Immune signaling pathways in Rhodnius prolixus in the context of Trypanosoma rangeli infection: cellular and humoral immune responses and microbiota modulation - Pereira, Suelen Bastos; Mattos, Débora Passos de; Gonzalez, Marcelo Salabert; Mello, Cicero Brasileiro; Azambuja, Patrícia; Castro, Daniele Pereira de; Vieira, Cecília Stahl (Frontiers in Physiology, 2024)
Introduction Rhodnius prolixus is a hematophagous insect and one of the main vectors for Trypanosoma cruzi and Trypanosoma rangeli parasites in Latin America. Gut microbiota and insect immune responses affect T. cruzi and T. rangeli infection within triatomines. Particularly the Toll and IMD signaling pathways activations and how they orchestrate the antimicrobial peptides (AMPs) expressions in R. prolixus, especially when infected by T. rangeli. Objectives Examine how T. rangeli infection modulates R. prolixus cellular and humoral immunity and its impacts on insect microbiota. Methods R. prolixus was fed on blood containing epimastigotes of T. rangeli, and infection was quantified in insect tissues. The gene expression of dorsal, cactus, relish, PGRP, and AMPs was examined in the midgut, fat body, and salivary glands by quantitative real-time PCR. Microbiota composition was analyzed using RT-q PCR targeting specific bacterial species. Hemocyte numbers and phenoloxidase activity were quantified to assess cellular immune responses. Results T. rangeli infection modulated triatomine immunity in midgut and hemocoel, activating the expression of the NF-kB gene dorsal, associated with the Toll pathway; increasing expression of the gene encoding PGRP receptor, a component involved in the IMD pathway, both in the intestine and fat body; repressing the expression of the relish transcription factor, mainly in salivary glands. Among the R. prolixus AMPs studied, T. rangeli infection repressed all AMP gene expression, other than defensin C which increased mRNA levels. The PO activity was enhanced in the hemolymph of infected insects. T. rangeli infection did not induce hemocyte number alterations compared to control insects. However, an increase in hemocyte microaggregation was detected in infected insects. Discussion R. prolixus recognizes T. rangeli infection and triggers humoral and cellular immune responses involving Toll pathway activation, defensin C synthesis, increased phenoloxidase activity, and enhanced hemocyte aggregation. On the other hand, T. rangeli infection suppressed some IMD pathway components, suggesting that, in R. prolixus, this pathway is involved in defensins A and B gene regulation. Importantly, these immune responses altered the bacterial microbiota composition, potentially favoring T. rangeli establishment in the insect vector.